Influence of Blood Purification and Differential Injection Sites of Cold Saline on Transpulmonary Thermodilution Values. Issue 3 (10th May 2018) - Kawaji, Takahiro; Sakai, Toshikazu; Moriyama, Kazuhiro; Hara, Yoshitaka; Nakamura, Tomoyuki; Kuriyama, Naohide; Shimomura, Yasuyo; Kato, Yu; Komura, Hidefumi; Yamashita, Chizuru; Kurimoto, Yasuyoshi; Hasegawa, Daisuke; et al.
Abstract: We aimed to investigate the effects of blood purification and cold saline injection sites on the transpulmonary thermodilution values. We measured the cardiac output of eight pigs in every combination of cold saline injection (left jugular and femoral veins) and blood purification sites (right jugular and femoral veins), with or without blood purification. We examined the influence of the difference between the presence and absence of blood purification, vascular sites for blood purification, and sites for cold saline injection on the transpulmonary thermodilution values. Cardiac output measured during blood purification using transpulmonary thermodilution was underestimated; however, there was no difference between vascular sites. Cardiac output measured via injection of cold saline into the femoral vein was higher than that obtained through injection of cold saline into the jugular vein, with or without blood purification.